Impact of Conflict and Job Stress at Work at Home Mom performance During Pandemic Covid 19 in Medan - Rini Astuti; Hasrudy Tanjung; Meiriyand Ananda Amin Surya; Delyana Rahmawany (AIBPM Publisher, 2021)
Conducted research to understand work-family conflict and stress at work affects the performance of mothers who work at home during COVID-19 pandemic in Medan City. And what is work family conflict and work stress simultaneously affect the performance of mothers who work at home. Population in this research is mothers who work at home during the Covid-19 Pandemic as many as 100 people are drawn at random. Using multiple linear regression, test the assumptions classic, t test, f test and coefficient of determination. The results of this study show that the Work. variable Family Conflict and stress at work partially affect performance mothers who work at home as well as simultaneously family work conflict and work stress have a significant effect on the performance of mothers working at home during the pandemic Covid 19 in Medan City.